2015
DOI: 10.1016/j.cell.2015.02.014
|View full text |Cite
|
Sign up to set email alerts
|

The RNA Binding Protein Quaking Regulates Formation of circRNAs

Abstract: Circular RNAs (circRNAs), formed by non-sequential back-splicing of pre-mRNA transcripts, are a widespread form of non-coding RNA in animal cells. However, it is unclear whether the majority of circRNAs represent splicing by-products without function or are produced in a regulated manner to carry out specific cellular functions. We show that hundreds of circRNAs are regulated during human epithelial-mesenchymal transition (EMT) and find that the production of over one-third of abundant circRNAs is dynamically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

31
1,605
4
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,758 publications
(1,646 citation statements)
references
References 47 publications
31
1,605
4
6
Order By: Relevance
“…These observations are consistent with previous reports by Guo et al and Conn et al that the majority of circRNAs do not act as miRNA sponges. 14,42 We estimated that for every 2580 molecules of ICAM-1, there is 1 molecule of mcircRas-GEF1B (Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…These observations are consistent with previous reports by Guo et al and Conn et al that the majority of circRNAs do not act as miRNA sponges. 14,42 We estimated that for every 2580 molecules of ICAM-1, there is 1 molecule of mcircRas-GEF1B (Fig. S3).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of circRNAs have been identified in various cell lines and across different species as a result of high-throughput sequencing and novel computational approaches. 2 Accumulating evidence indicates that circRNAs are not just by-products of missplicing or splicing errors but instead are processed through regulated back-splicing involving distinct sets of cis-elements and/or trans-factors, [3][4][5] suggesting that they possess biological functions. Importantly, circRNAs have been shown to be involved in gene expression regulation as microRNA (miRNA) sponges.…”
mentioning
confidence: 99%
“…We would anticipate that essential factors for circRNA biogenesis are someway ubiquitously expressed, but QKI5 is not expressed in all cells. Thirdly, flanking complementary sequences are associated with more than half of the circRNAs, and QKI5 has not been tested for biogenesis of circRNAs with flanking complementary repeats [8]. Some circRNAs showed cell type or tissue specific expression between two cells under comparison, even when their parent genes might be expressed (as mRNA) in both cells [7].…”
mentioning
confidence: 99%
“…There are also disputes about whether circRNAs are generated co-transcriptionally or post-transcriptionally [5,6]. A recent publication showed that the RNA-binding protein quaking I 5 (QKI5) might participate in the circularization [8], although we have to keep in mind with several points before considering QKI5 as an essential player in circRNA biogenesis. First, QKI5 is a known regulatory factor of alternative splicing for selective mRNAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation